Economic Efficiency of Cultivating the ‘Yog‘Du’ Variety of Rarely Distributed Peking Cabbage Belonging to the Brassicaceae Family - Kholmamatovich, Khurramov Ulug‘bek; Rayimovich, Khurramov Olim; Azizjon oglu, Jumanov Laziz (American Journal of Biodiversity, 2026)
The article highlights the economic efficiency of cultivating the new “Yog‘du” variety of Peking cabbage. The efficiency of growing Peking cabbage in open fields and protected cultivation areas under early and mid-season planting dates was determined, including net profit and profitability indicators.